2011
DOI: 10.1124/jpet.111.178988
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Actions of Endothelin A-Selective Versus Combined Endothelin A/B Receptor Antagonists in Early Diabetic Kidney Disease

Abstract: Selective endothelin A (ET A ) and combined ET A and ET B receptor antagonists are being investigated for use in treating diabetic nephropathy. However, the receptor-specific mechanisms responsible for producing the potential benefits have not been discerned. Thus, we determined the actions of ET A and ET B receptors on measures of glomerular function and renal inflammation in the early stages of diabetic renal injury in rats through the use of selective and combined antagonists. Six weeks after streptozotocin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 39 publications
(53 reference statements)
3
61
1
Order By: Relevance
“…A prolonged and possibly exacerbated vasoconstriction 29 after ET-B antagonism may have also helped to aggravate MV rarefaction, which may have contributed to the persistence of renal fibrosis. Therefore, because ET-A blockade had a significant hemodynamic effect on the PTRAS-treated kidney that led to recover renal function, it is possible that the combination of vasoconstriction and enhanced progrowth activity after addition of ET-B blockade may have expanded renal damage, 32,33 which may have, consequently, blunted the effect of PTRAS.…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged and possibly exacerbated vasoconstriction 29 after ET-B antagonism may have also helped to aggravate MV rarefaction, which may have contributed to the persistence of renal fibrosis. Therefore, because ET-A blockade had a significant hemodynamic effect on the PTRAS-treated kidney that led to recover renal function, it is possible that the combination of vasoconstriction and enhanced progrowth activity after addition of ET-B blockade may have expanded renal damage, 32,33 which may have, consequently, blunted the effect of PTRAS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a direct adverse effect of VEGF inhibition on podocyte function and expression of slit-diaphragm proteins, ET-1 can exert negative effects on podocyte function, which, additionally to the disruption of VEGF pathway, may contribute to glomerular injury and proteinuria. 10,11,31,32 For instance, a subpressor dose of ET-1 administered to SpragueDawley rats was found to increase glomerular permeability and inflammation, as well as nephrinuria, effects that could be blocked by an endothelin receptor type A antagonist. 31 In cultured podocytes, ET-1 through activation of endothelin receptor type A induces nephrin shedding concomitant with a redistribution of the podocyte's cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,31,32 For instance, a subpressor dose of ET-1 administered to SpragueDawley rats was found to increase glomerular permeability and inflammation, as well as nephrinuria, effects that could be blocked by an endothelin receptor type A antagonist. 31 In cultured podocytes, ET-1 through activation of endothelin receptor type A induces nephrin shedding concomitant with a redistribution of the podocyte's cytoskeleton. 10 Recently, Buelli et al 11 have shown activation of the β-arrestin-1 signaling pathway by ET-1, resulting in transition of podocytes from an epithelial to mesenchymal cell type.…”
Section: Discussionmentioning
confidence: 99%
“…9 Finally, several studies have shown that ET receptor antagonists ameliorate experimental diabetic nephropathy. 8,12,13 It is within this context that two papers in this issue of JASN are of special interest: an experimental study that elucidates the functional significance of the ET A and ET B receptors on podocytes in diabetic kidney injury and a complementary clinical study demonstrating the antiproteinuric effects of an ET antagonist in diabetic nephropathy.…”
mentioning
confidence: 99%
“…9 Finally, several studies have shown that ET receptor antagonists ameliorate experimental diabetic nephropathy. 8,12,13 It is within this context that two In the experimental study, Lenoir et al 14 used a novel mutant mouse wherein podocyte-specific, double deletion of the ET A and ET B receptors was induced. They not only demonstrated that these mice were protected against diabetes-induced podocyte loss and the attendant glomerulosclerosis but also provide evidence that the ET B receptor may play as important a role as does the ET A receptor; this finding challenges the widely held notion that the deleterious effects of ET in diabetes are due to activation of the ET A receptor.…”
mentioning
confidence: 99%